4(5(-8)+4)=9((-8)-8)

Simple and best practice solution for 4(5(-8)+4)=9((-8)-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(5(-8)+4)=9((-8)-8) equation:


Simplifying
4(5(-8) + 4) = 9((-8) + -8)

Multiply 5 * -8
4(-40 + 4) = 9((-8) + -8)

Combine like terms: -40 + 4 = -36
4(-36) = 9((-8) + -8)

Multiply 4 * -36
-144 = 9((-8) + -8)
-144 = 9(-8 + -8)

Combine like terms: -8 + -8 = -16
-144 = 9(-16)

Multiply 9 * -16
-144 = -144

Add '144' to each side of the equation.
-144 + 144 = -144 + 144

Combine like terms: -144 + 144 = 0
0 = -144 + 144

Combine like terms: -144 + 144 = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| -10+2y=8+4y | | 7(y+1)=6y-9 | | Ht=-16t^2+35+ho | | -8t=-3-5t | | 18y-405=99 | | 10-b=9b-10 | | 4c-2=8c-10 | | 2+8=-5(6x-2) | | -p=-7-2p | | 9x-38+21y-1=180 | | 3x+-5=7x+7 | | 8+g=-10-2g | | 24+0.20x=x | | 19=(x/8) | | 2r=7+3r | | 2x+14=3x-11 | | 2v-3-11v=-6(1+19v)+-6(-18v-11) | | -8d=8-6d | | 3n=2+5n | | 5x+14=4x | | C=37.03+0.25x | | 5k=-6+6k | | 3(m-15)=m-7 | | -q-10=-2q | | x+80+50+x+60=180 | | 28+5=44 | | 22=n-(-4) | | 7x+7(2x-9)=63 | | g(x)=3x^2+9x | | 6y-9=7 | | 8x+7x=16 | | 7(x+1)+3(4+x)-7= |

Equations solver categories